Initial Incomplete Thermal Ablation Is Associated With a High Risk of Tumor Progression in Patients With Hepatocellular Carcinoma - Tan, Jie; Tang, Tian; Zhao, Wei; Zhang, Zi-Shu; Xiao, Yu-Dong (Frontiers in Oncology, 2021)
Purpose: To investigate whether incomplete thermal ablation is associated with a high risk of tumor progression in patients with hepatocellular carcinoma (HCC), and to compare the efficacy of repeated thermal ablation and transarterial chemoembolization (TACE) for residual tumor after incomplete ablation. Methods: This retrospective study included 284 patients with unresectable HCC who underwent thermal ablation. The response of the initially attempted ablation was classified into complete (n=236) and incomplete (n=48). The progression-free survival (PFS) and overall survival (OS) were compared between patients with complete and incomplete responses, before and after a one-to-one propensity score-matching (PSM), and between patients in whom repeated ablation or TACE was performed after a first attempt incomplete ablation. Results: After PSM of the 284 patients, 46 pairs of patients were matched. The PFS was significantly higher in the complete response group than in the incomplete response group (P<0.001). No difference in OS was noted between two groups (P=0.181). After a first attempt incomplete ablation, 29 and 19 patients underwent repeated ablation and TACE, respectively. There were no significant differences in PFS (P=0.424) and OS (P=0.178) between patients who underwent repeated ablation and TACE. In multivariate Cox regression analysis, incomplete response (P˂0.001) and Child-Pugh class B (P=0.017) were independent risk factors for tumor progression, while higher AFP level (P=0.011) and Child-Pugh class B (P=0.026) were independent risk factors for poor OS. Conclusion: Although patients with incomplete ablation are associated with tumor progression compared with those with complete ablation, their OS is not affected by incomplete ablation. When patients present with residual tumors, TACE may be an alternative if repeated ablation is infeasible.